Cbx3 inhibits vascular smooth muscle cell proliferation, migration, and neointima formation. Issue 3 (30th November 2017) - Zhang, Cheng; Chen, Dan; Maguire, Eithne Margaret; He, Shiping; Chen, Jiangyong; An, Weiwei; Yang, Mei; Afzal, Tayyab Adeel; Luong, Le Anh; Zhang, Li; Lei, Han; Wu, Qingchen; et al.
Abstract: Aims: To investigate the role of chromobox protein homolog 3 (Cbx3) in vascular smooth muscle cell (VSMC) proliferation, migration, and neointima formation following vascular injury. Methods and results: Overexpression of Cbx3 led to a significant increase in VSMC contractile gene expression and VSMC apoptosis as well as a dramatic decrease in collagen gene expression, VSMC proliferation, and migration. Meanwhile, the opposite was observed following inhibition of endogenous Cbx3. Luciferase activity assays revealed that Notch signalling, but neither β-catenin nor NF-κB signalling, is regulated by Cbx3 in VSMCs, and among the four Notch receptors, Notch3 is selectively down-regulated by Cbx3 through a transcriptional repression mechanism. Notch3 gene activation recapitulates the effects of Cbx3 knockdown on VSMC proliferation and migration. Consequently, the inhibitory effects of Cbx3 over-expression on VSMC proliferation and migration were reversed by Notch3 gene reactivation. In a model of vascular damage by carotid wire injury, we observed that Cbx3 expression was dramatically down-regulated in the injured arteries. Local ectopic over-expression of Cbx3 in the injured arteries significantly inhibited Notch3 expression, thereby reducing VSMCs proliferation and causing an overall decrease in neointima formation. Additionally, injury-induced neointimal SMC hyperplasia was significantly reduced by aortic inhibition of Notch3. Importantly, a decreased expression level of Cbx3, but an increased expression level of Notch3, was observed in human femoral arteries with atherosclerotic lesions. Conclusion: Cbx3 modulates VSMC contractile and collagen gene expression, as well as VSMC proliferation, migration, and apoptosis via a Notch3 pathway, and plays an important role in controlling injury-induced neointima formation.